A Geospatial Mixed Methods Approach to Assessing Campus Safety. (October 2013) - Hites, Lisle S.; Fifolt, Matthew; Beck, Heidi; Su, Wei; Kerbawy, Shatomi; Wakelee, Jessica; Nassel, Ariann
Background: While there is no panacea for alleviating campus safety concerns, safety experts agree that one of the key components to an effective campus security plan is monitoring the environment. Despite previous attempts to measure campus safety, quantifying perceptions of fear, safety, and risk remains a challenging issue. Since perceptions of safety and incidents of crime do not necessarily mirror one another, both were utilized in this investigation. Purpose: The purpose of this article is to describe an innovative, mixed methods approach for assessing campus safety at a large, urban campus in the southeast region of the United States. Method: A concurrent triangulation design was implemented to allow investigators the opportunity to collect qualitative and quantitative data simultaneously and integrate results in the interpretation phase. Data were collected from four distinct sources of information. Results: Student focus groups yielded data regarding perceptions of risk, and kernel density analysis was used to identify "hot spots" of campus crime incidents. Conclusion: While in many cases perceived risk and actual crime incidents were associated, incidents of hot spots of each type occurred independently with such frequency that an overall correlation of the two was not significant. Accordingly, while no significant correlation between perceived risk and crime incidents was confirmed statistically, the geospatial integration of these data suggested three types of safety conditions. Further, the combination of focus group data and spatial analyses provided a more comprehensive and, therefore, more complete understanding of the multifaceted issues related to campus safety.